2007
DOI: 10.1111/j.1526-4610.2007.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuron–Glia Signaling in Trigeminal Ganglion: Implications for Migraine Pathology

Abstract: Objective.-The goal of this study was to investigate neuronal-glial cell signaling in trigeminal ganglia under basal and inflammatory conditions using an in vivo model of trigeminal nerve activation.Background.-Activation of trigeminal ganglion nerves and release of calcitonin gene-related peptide (CGRP) are implicated in the pathology of migraine. Cell bodies of trigeminal neurons reside in the ganglion in close association with glial cells. Neuron-glia interactions are involved in all stages of inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
290
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(311 citation statements)
references
References 54 publications
19
290
1
1
Order By: Relevance
“…In the periphery, release of CGRP from trigeminal fibers is believed to cause vasodilation and mast cell degranulation, ultimately resulting in a persistent pro-inflammatory sensitization of trigeminal nociceptors [53][54][55]. Studies have suggested that CGRP release works in a paracrine manner, causing excitation of nearby neuronal and satellite glial cells and stimulating its own synthesis [56]. This cascade of events supports the role of CGRP in the development and maintenance of peripheral and central sensitization in migraine pathogenesis [20].…”
Section: Functionmentioning
confidence: 68%
“…In the periphery, release of CGRP from trigeminal fibers is believed to cause vasodilation and mast cell degranulation, ultimately resulting in a persistent pro-inflammatory sensitization of trigeminal nociceptors [53][54][55]. Studies have suggested that CGRP release works in a paracrine manner, causing excitation of nearby neuronal and satellite glial cells and stimulating its own synthesis [56]. This cascade of events supports the role of CGRP in the development and maintenance of peripheral and central sensitization in migraine pathogenesis [20].…”
Section: Functionmentioning
confidence: 68%
“…The resulting depression, anxiety, sleep fragmentation, allodynia, and hyperalgesia characterize a number of chronic pain disorders. [2][3][4][5][6][7][8][9][10][11][12][13] At least two etiological pathways are posited for central sensitization. The first is chronification of nociceptive pain; and involves neuroplastic changes, and peripheral sensitization as precursors to central sensitization and the resulting clinical pain.…”
Section: What Is Central Sensitization (Cs)mentioning
confidence: 99%
“…This contributes to the fatigue and malaise often associated with CSS. [5,12,14,20,21,[23][24][25][33][34][35][36][37][38] Utilizing the resultant depression, anxiety, hyperalgesia, allodynia, stress related pain exacerbation, fatigue, and poor sleep, we can establish a list of indicators for central sensitization. Taken alone, with the possible exception of allodynia and stress related pain, none of these are pathognomonic.…”
Section: Diagnosis Therapy and Prognosismentioning
confidence: 99%
See 2 more Smart Citations